Equine nutrition and feeding - Frape, David , 1929- (Wiley-Blackwell, 2010)
Equine Nutrition and Feeding is the seminal work on the subject. It covers all the key topics needed for equine nutrition degree course. This comprehensive and clearly evidenced textbook covers how food is digested and nutrients are used in growing, working and breeding horses